Complexity in project co-creation of knowledge for innovation - Harri Ruoslahti (Journal of Innovation & Knowledge (JIK), 2020)
The European Union (EU) promotes collaboration across functions and borders in its funded innovation projects, which are seen as complex collaboration to co-create knowledge. This requires the engagement of multiple stakeholders throughout the duration of the project. To probe complexity in EU-funded innovation projects the research question is: How does complexity affect the co-creation of knowledge in innovation projects, according to project participants? The data for this study was collected from project experts in the form of short narratives, using a questionnaire based on the elements of complexity of Mitleton-Kelly (2003). The results indicate that complexity characterises the co-creation of knowledge in innovation projects in various ways. Most emphasis was put on the elements Self-organisation, Connectivity and interdependence, Co-evolution, and Creation of new order. Thus, although this study demonstrates that the elements of complexity can be used to gain insight into innovation projects, the results show that not all elements of complexity are equally important in this context and that they appear in a certain order. Moreover, understanding the complexity of collaboration for innovation in relation to the input-throughput-output model of organisational communication is a contribution to theory that may help future projects achieve faster innovation.
Keywords: 650; Co-creation; Complexity; Innovation projects; Time-to-innovation